2004
DOI: 10.1111/j.1095-8312.2004.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in the long-nosed snake, Rhinocheilus lecontei (Colubridae): beyond the subspecies debate

Abstract: Scalation, colour pattern, linear and geometric morphometrics were used to quantify geographical differentiation in the long-nosed snake, Rhinocheilus lecontei, and to test the hypothesis that all four subspecies are morphologically distinct. Also investigated were potential associations between morphological (scalation, colour pattern, linear measurements) and environmental variables (climate, vegetation, soil). Sexual dimorphism was weakest for geometric and strongest for linear morphometric variables. Morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 27 publications
0
36
1
4
Order By: Relevance
“…A different pattern is observed in snakes, although the reduced number of studies once again hinders the extraction of definite conclusions. The available studies indicate that head/skull shape SD in snakes is non-existent or of relatively low importance, at least as compared to other sources of variation, such as geographic locality (MAnIEr, 2004;SMITH & coLLyEr, 2008) or phylogenetic signal (GEnTILLI et al, 2009). clearly, patterns of shape SD and its variation in turtles and snakes needs to be further investigated in the future.…”
Section: Sexual Dimorphismmentioning
confidence: 99%
“…A different pattern is observed in snakes, although the reduced number of studies once again hinders the extraction of definite conclusions. The available studies indicate that head/skull shape SD in snakes is non-existent or of relatively low importance, at least as compared to other sources of variation, such as geographic locality (MAnIEr, 2004;SMITH & coLLyEr, 2008) or phylogenetic signal (GEnTILLI et al, 2009). clearly, patterns of shape SD and its variation in turtles and snakes needs to be further investigated in the future.…”
Section: Sexual Dimorphismmentioning
confidence: 99%
“…Although the application of geometric morphometrics in SD studies still needs to be explored, some authors report interesting SD patterns revealed by the application of such techniques in various animal taxa (Hood, 2000;Rosas and Bastir, 2002;Loy et al, 2004;Rufino et al, 2004;Valenzuela et al, 2004;Bruner et al, 2005). Until the present, geometric methods have not been extensively applied to study the external morphology of lizards, and very few authors have applied such methods in reptiles (Monteiro et al, 1997;Claude et al, 2003;Marugá n-Lobón and Buscalioni, 2003;Manier, 2004;Bruner et al, 2005;Stayton, 2005;Vidal et al, 2005). In the case of lacertid lizards, geometric morphometrics could be of great use, since SD patterns in this group involve sexual variation in head dimensions and shape.…”
mentioning
confidence: 99%
“…6). A pesar de que con los dos métodos morfométricos, tradicionales y geométricos, no es posible hacer comparaciones directas (Manier 2004) sí es posible realizar algunas relaciones. Por ejemplo, el ancho y largo de la cabeza en el análisis de CP de medidas lineales es el caracter que presenta mayor peso y, con la placa fina de deformación resultante de la configuración de landmarks, se puede apreciar que, la variación se encuentra relacionada con este carácter; como se refiere a continuación para cada una de las poblaciones que mostraron diferencias significativas.…”
Section: Resultsunclassified
“…(Manier 2004). Un primer paso es evaluar los caracteres diagnósticos de las subespecies existentes, para ello se han utilizado diversos métodos que permiten evaluar desde otra perspectiva los caracteres morfológicos diagnósticos.…”
Section: Introductionunclassified
See 1 more Smart Citation